Report on UNESCO's awareness raising and capacity building actions in the SmartCulTour Living Labs - Fidelbo, Costanza; Rosati, Matteo; Debrine, Peter; Nikolić Đerić, Tamara; Petrić, Lidija; Mandić, Ante; Björn, Ella; Lozano, Diego; Kerst, Iris; Neuts, Bart; Lioce, Raffaella; Bettin, Michele (Zenodo, 2023)
This report presents the awareness raising and capacity building actions implemented by UNESCO in the six SmartCulTour Living Labs, namely the Split Metropolitan area (Croatia), the Utsjoki ( Ohcejohka in North Sami) Municipality (Finland), the Huesca province (Spain), the Rotterdam Metropolitan Region (Netherlands), the Scheldeland region in Flanders (Belgium), and the city of Vicenza (Italy). In the context of SmartCulTour, and as Leader of Work Package 6, UNESCO is responsible for the overall coordination of the Living Labs, as well as for raising awareness and developing capacities of concerned stakeholders to harness the collective benefits of culture and tourism for society. This was pursued by presenting and promoting participatory, inclusive, people-centred, needs-driven and context-specific approaches to the sustainable integration of culture and tourism into local development practices. This report presents, in a chronological order, the relevant activities organized in and with the six LLs throughout 2022, as follows: Split Living Lab: 4 appointments, online and in-person, between February and April; Utsjoki Living Lab: 3 appointments, online and in-person, between April and October; Huesca Living Lab: 2 appointments, online and in-person, in October; Rotterdam Living Lab: 1 in-person appointment in October; Scheldeland Living Lab: 1 in-person appointment in October; Vicenza Living Lab: 1 in-person appointment in November. The presentation of the actions stems from the background situational analysis of each destination, including potential entry points with regards to the LLs’ workplan implemented so far. This combined elements spurred the choice of specific training topics, while representing the underlying reasons for the adoption of context-sensitive approaches to each LL. The central role of stakeholders was a cross-cutting consideration in the design of the capacity building programmes, and it constitutes a focus across the reports, in terms of expressed interests, identified knowledge gaps, and ...